Agriculture, economics, and resource management - Snodgrass, Milton Moore; Wallace, Luther T. (Englewood Cliffs, N.J. : Prentice-Hall, 1975)
Agriculture, economics, and resource management by Milton M. Snodgrass, L. T. Wallace has several objectives: provide a material for resources use management in agriculture; exposition of microeconomic principles and other business management tools used in decision making; present, some physical and human resource adjustment; and provide relevant data for the interpretation and analysis.
Published in 1964 and 1970 under title: Agriculture, economics, and growth.
Includes bibliographical references and index.
lje 29/01/2018
Loans
Keywords: Agriculture; Economics; Management